Functional nanostructure-loaded three-dimensional graphene foam as a non-enzymatic electrochemical sensor for reagentless glucose detection. Issue 56 (11th September 2020) - Liu, Qianshi; Zhong, Huage; Chen, Miao; Zhao, Chang; Liu, Yan; Xi, Fengna; Luo, Tao
Abstract : A non-enzymatic electrochemical sensor was fabricated by loading functional nanostructure on three-dimensional graphene foam for reagentless detection of glucose with high sensitivity and stability. Abstract : Non-enzymatic and reagentless electrochemical sensors for convenient and sensitive detection of glucose are highly desirable for prevention, diagnosis and treatment of diabetes owing to their unique merits of simplicity and easy operation. Facile fabrication of a three-dimensional (3D) sensing interface with non-enzymatic recognition groups and an immobilized electrochemical probe remains challenge. Herein, a novel non-enzymatic electrochemical sensor was developed for the sensitive and reagentless detection of glucose by loading functional nanostructure on 3D graphene. Monolithic and macroporous 3D graphene (3DG) foam grown by chemical vapor deposition (CVD) served as the electrode scaffold. Prussian blue (PB) and gold nanoparticles (AuNPs) were first co-electrodeposited on 3DG (3DG/PB-AuNPs) as immobilized signal indicator and electron conductor. After a polydopamine (PDA) layer was introduced on 3DG/PB-AuNPs via facile self-polymerization of dopamine to stabilize internal PB probes and offer chemical reducibility, the second layer of AuNPs was in situ formed to assemble the recognition ligand, mercaptobenzoboric acid (MPBA). Owing to the high stability of PB and good affinity between MPBA and glucose, the non-enzymatic sensor was able to be used in reagentless detection of glucose with high selectivity, wide linear range (5 μM–65 μM) and low detection limit (1.5 μM). Furthermore, the sensor was used for the detection of glucose level in human serum samples.